Seismic Analysis of RCC Building (G+2) Using Staad Pro (International Journal of Innovative Research in Computer Science & Technology, 2022)
Earthquakes signal a change in the earth's  internal structure. Seismic activity is frequent in most  places of the world, albeit the frequency with which it  occurs is dependent on the tectonic configuration of the  area. Previous earthquakes have resulted in significant  loss of life and property, impacting a country's social and  economic conditions. Though an earthquake cannot be  avoided, the least that can be done to minimise damage is  to make buildings earthquake resistant. As our  understanding of earthquakes has improved, most  countries have enforced the inclusion of seismic  precautions in building design and architecture. In the  event of an earthquake, seismic waves from the epicentre  are propagated across the entire region. The effects of  lateral loads like as earthquake loads, wind loads, and  blast forces have been a major issue in recent years. One  of the key issues that every designer faces is providing  sufficient strength and stability in the face of lateral  stresses. As a result, structural engineers must have a  thorough understanding of the seismic performance of  various types of shear walls in order to protect the  structure against lateral loads. For (G+20) story’s, the  current paper compares the seismic performance of high rise structures and optimizes the thickness of RCC shear  wall, Steel Plate Shear Wall (SPSW), and composite  shear wall. The design and analysis of the building with  RCC shear wall, steel plate shear wall and composite  shear wall is carried out using software ETABS or  STAADPRO. Effect of varying thickness of shear panels  and comparison of the results of story drift and story  shear is presented. The main goal of this project is to use  STAAD Pro to study and design a multi-story structure  [G + 2 (3 dimensional frame)]. The design entails load  calculations and a STAAD Pro analysis of the entire  structure. Limit State Design, as defined by the Indian  Standard Code of Practice, was employed in the  STAAD.Pro analysis. STAAD.Pro comes with a cutting edge user interface, visualization tools, and sophisticated  analysis and design engines that can do complex finite  element and dynamic analysis. STAAD.Pro is the  professional's choice for model generation, analysis, and  design, as well as visualisation and result verification.  Initially, we evaluated and constructed a G + 1 story  building [2-D Frame] for all load combinations [dead and  live].STAAD.Pro offers a very user-friendly interface that  allows users to sketch the frame and enter load values and  dimensions. The structure is then analyzed and members  with reinforcement details for RCC frames are designed  based on the supplied criteria. The accurate analysis and  design of a G + 2 3-D RCC frame under various load  combinations is the final job. A 3-D RCC frame with  three bays has been considered. G + 2 floors made up the  y-axis. Each floor has 137 beams and 140 columns, for a  total of 137 beams and 140 columns. The ground floor  was 3.5 meters tall, and the other two story’s were also  3.5 meters tall. Under self-weight, dead load, and live  load conditions, the structure was tested. The ground  floor height was 3.5m and rest of the 2 floors had a height  of 3.5m.The structure was subjected to self weight, dead  load, live load under the load case details of STAAD.Pro.  The materials were specified and cross-sections of the  beam and column members were assigned.The fixed  supports at the structure's base were also defined. For  design purposes, the codes of practice to be followed  were also stated, along with other relevant aspects. The  structure was then analyzed and the members were  designed using STAAD.Pro. After completing the design,  we may work on the structure and investigate the bending  moment and shear force values using the generated  diagrams in the post-processing mode. We've also looked  at the deflection of different parts under various loading  scenarios. The building's design is dictated by the  minimum standards set forth in the Indian Standard  Codes. Building structural safety regulations are set to the  bare minimum. Are being covered by way of laying down  minimum design loads which have to be assumed for  dead loads, imposed loads, and other external loads, the  structure would be required to bear. Strict conformity to  loading standards recommended in this code, it is hoped,  will ensure the structural safety of the buildings which are  being designed. Structure and structural elements were  normally designed by Limit State Method. Complicated  and high-rise structures need very time taking and  cumbersome calculations using conventional manual  methods. STAAD.Pro provides us a fast, efficient, easy to  use and accurate platform for analysing and designing  structure.
Keywords: Loads; Shear wall; Steel walls; STAAD Pro; ETABS